The child in me-dia understanding the experiences of adult fans of Disney - Tiangco, Rain F.
“Disney adults” have earned a reputation for being immature, obsessive, and self-infantilized in online discussions. Adults who engage with child-associated objects have generally been judged based on age norms, among other social norms. Investigating the long-term attachment to Disney of fans with a focus on the aspect of age, this research answered the question, “How do adult fans of Disney animated films engage and participate in fan culture?” with Deuze’s Media Life as a foundational concept, and integrating the theories of Jenkins’ Fandom, Arnett’s Emerging Adulthood, and Hills’ Fandom as a Transitional Object (TO). Narratives of six participants aged 19–23 were attained through in-person interviews, and I, as a researcher and fan, expanded on the emerging themes through autoethnography. The findings reflect the depth of Disney’s role in participants’ lives through the provision of nostalgia-related comfort, association with meaningful memories of the self and family, and deeply ingrained incorporation into their current identity. This study builds on the discourse on the media life of Gen Z, suggests an alternative approach to the concept of the TO in media studies, and forwards the foundational impact of media and play on people’s development.